Adverse Drug Reactions in Drug-Resistant Tuberculosis Management: A Clinical Approach - Babu, Leya P; Babu, Johnson V; George, Shaji; Robin, Nimmy; Jose, Joicy (Journal of Pharmacy Practice and Community Medicine)
Tuberculosis is a contagious disease caused by Mycobacterium tuberculosis, leading to increased mortality and morbidity. Although many new diagnostic tests and treatments have emerged for TB, there is still a big question as to why it is not ending. The disease roots easily due to many confounding factors such as patient noncompliance, development of ADR during treatment and the evolution of drug resistance, etc. The drugs used in treatment have a higher proportion of side effects; hence, the incidence of ADR also escalates due to polypharmacy, extended duration of treatment and the dose used. For identification and prevention, close monitoring should be done. ATT induced adverse effects are a leading cause of death and the reason for prolonged treatment, thus, this may result in noncompliance and treatment failure. The aim was to address the clinical approach of ADR caused by the anti-tubercular drug. The most common ADR reported were gastritis, hepatitis, hypersensitivity reactions and the major causative agent is pyrazinamide. Majority of patients required treatment modification due to ADRs. Sometimes the ADR developed is unnotified and can lead to a serious reaction. If the ADR is properly monitored and reported, it may minimize morbidity and better therapeutic outcomes can be achieved. More than 20% of patients developing negative outcomes due to ADR and about 15-18% of patient’s therapy were stopped due to ADR. Proper identification, reporting, management, or prevention can increase compliance and positive outcomes of therapy.
Keywords: Tuberculosis; Drug-resistant Tuberculosis; ADR Management; Tuberculosis drugs; Tuberculosis treatment.